Migraine, Botulinum Toxin type-A, and the Disappearing Sebaceous Cyst - Turner, Ira M.; Agrillo, Tiffany (Headache, 2005)
Botulinum toxin type-A has been used with increasing frequency as a migraine prophylactic agent. A recent case of ours had an unexpected beneficial effect on a local comorbid condition.Botulinum toxin type-A has been used with increasing frequency as a migraine prophylactic agent. A recent case of ours had an unexpected beneficial effect on a local comorbid condition.